A Remote Sensing Approach for Displaying the Changes in the Vegetation Cover at Az Zakhnuniyah Island at Arabian Gulf, Saudi Arabia. (17th March 2022) - Al-Taisan, Wafa'a A.
Abstract : In the terrestrial ecosystem, vegetation is the important component of exchanging of water and energy in biogeochemical and climate cycle. A study was conducted to detect the vegetation cover change at Az Zakhnuniyah island by using remote sensing techniques. It includes vegetation analysis using normalized difference vegetation index (NDVI) while comparing with climatological data including temperature, humidity, and precipitation. A clear trend was seen in climatological parameters where temperature and humidity were rising decade by decade although NDVI did not show. In addition, increasing soil salinization over the years was observed when soil salinity index was used. NDVI-based long-term decadal analysis on vegetation cover based on Landsat surface reflectance data showed increase of vegetation cover which was also linked to precipitation trends. Also, the short-term demi-decadal comparison using PROBA-V showed the vegetation cover reduction between 2015 and 2019. Nevertheless, the sea level surrounding the island also showed an increasing trend of 0.34 cm/y, which could be the cause of inundation in some parts of the island in future. Furthermore, all these trends need to be observed in entirety as many of those trends can be interlinked.